Prototypes of Faith: Findings with the Faith Q-Sort - Wulff, David M. (Journal for the scientific study of religion, 2019)
Defining religion and finding ways to assess it in individual lives has long challenged psychologists of religion. At first, open-ended questionnaires were used, but with the advent of modern statistical methods, a succession of religiosity scales was developed. But these usually brief scales were typically based on the preconceptions of their authors, who were overwhelmingly Protestant Christian and often conservative, much as were those who completed them. To provide a more adequate way of assessing "faith," a term here encompassing both religious and nonreligious attitudes, a new assessment device was developed that incorporates the singular advantages of Q methodology. The Faith Q-Sort consists of 101 statements that respondents sort on a nine-category continuum, indicating the degree to which each statement describes himself or herself. Factor analysis based on correlations of the sorts rather than individual items yielded, for the initial group of participants, three major prototypes and five minor ones, accounting for 67 percent of the variance. Of the 42 participants, 31 proved to be exemplars of one or another of the eight prototypes. Subsequent explorations illustrate the wealth of possibilities the FQS offers, both as a research instrument and a counseling tool.